2006
DOI: 10.1007/s00464-005-0473-2
|View full text |Cite
|
Sign up to set email alerts
|

Omentum prevents intestinal adhesions to mesh graft in abdominal infections and serosal defects

Abstract: Preservation of the greater omentum reduces the formation of intestinal adhesions, especially in cases with underlying infections and serosal defects in abdominal closures using mesh grafts. This could be beneficial in related clinical situations in lowering the rate of intestinal fistulas, erosions, and obstructions that can be attributed to the formation of adhesions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 31 publications
0
12
0
1
Order By: Relevance
“…However, the management of such defects is still controversially discussed. In routine clinical practice, serosal defects are commonly closed by absorbable single sutures to avoid intestinal fistula or leakage in the postoperative course [14,15].…”
Section: Introductionmentioning
confidence: 99%
“…However, the management of such defects is still controversially discussed. In routine clinical practice, serosal defects are commonly closed by absorbable single sutures to avoid intestinal fistula or leakage in the postoperative course [14,15].…”
Section: Introductionmentioning
confidence: 99%
“…Intestinal adhesion to mesh potentially has important clinical implications for increasing postoperative morbidity and even mortality attributable to adhesive intestinal obstruction in the rat. [20] Animal studies have shown that composite meshes caused less adhesions to intraabdominal organs compared with non composite meshes. [21][22][23][24] The procedure resembles that of Pacilli et al [4] , differing in the aspect of placing the drape on the inner surface of the silo.…”
Section: Discussionmentioning
confidence: 99%
“…The negative pressure removes inhibitory factors such as inflammatory cytokines and collagenases, that suppress wound healing, as well as removal of bacteria and purulent fluid. 2 Polytrauma patients develop a triad of hypothermia, coagulopathy and acidosis, which the massive transfusion protocol attempts to reverse. However infusion of several units leads to a dilutional effect on anticoagulant and prothrombotic factors, which is cumulative to the underlying Systemic Inflammatory Response Syndrome (SIRS), producing issues for the managing surgeon.…”
Section: Discussionmentioning
confidence: 99%
“…This could prove beneficial in major trauma patients, who are known to be relatively immunocompromised after the massive transfusion protocol. 2 Topical negative pressure application has been demonstrated to provide an effective adjunct for large abdominal wound management. The negative pressure removes inhibitory factors such as inflammatory cytokines and collagenases, that suppress wound healing, as well as removal of bacteria and purulent fluid.…”
Section: Discussionmentioning
confidence: 99%